2012
DOI: 10.2478/v10237-012-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Motivational Climate and Team Cohesion in Adolescent Athletes

Abstract: T his study was conducted to determine whether adolescent athletes' perceptions of their team's level and type of cohesion would be related to, or differ as a function of, their perceptions of their team's motivational climate. This hypothesized link was assessed using both group comparison and multivariate correlational analyses. Study participants (N = 351 adolescent athletes) were recruited from sports camps conducted for high school-aged athletes at universities, colleges, and other sport facilities throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
3
36
0
5
Order By: Relevance
“…This atmosphere seemed to have produced perceptions of a masteryoriented training climate, which generated an increase in cooperative learning among athletes. Horn et al 42 found that coach-initiated task-oriented climates are linked to high levels of perceived team cohesion, which could be promoted by cooperative work.…”
Section: Discussionmentioning
confidence: 99%
“…This atmosphere seemed to have produced perceptions of a masteryoriented training climate, which generated an increase in cooperative learning among athletes. Horn et al 42 found that coach-initiated task-oriented climates are linked to high levels of perceived team cohesion, which could be promoted by cooperative work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a strong motivation climate leads up to positive experiences and satisfaction in future athletic activities [43]. Mastery motivational climate is positively correlated to the need for developing ability, autonomy and interpersonal relationships [44], cohesiveness [45] and negatively correlated to stress [46].…”
Section: Motivational Climatementioning
confidence: 99%
“…Researchers who have examined coaching attitudes and focused on training coaches to use a mastery motivational climate approach to coaching, including the promotion of prosocial behaviour, have demonstrated a positive impact on attendance at training, attitude towards the sport and coach, motivation, and perceptions of team cohesion (Bardel et al, 2010;Gould, Flett, & Lauer, 2012;Horn, Byrd, Martin, & Young, 2012;McLaren et al, 2015;Smith et al, 2007). The quality of relationships has also been found to be significant when examining parental influences on a young person's engagement in and enjoyment of sport.…”
Section: Resiliencementioning
confidence: 99%
“…Including the coaching staff strengthens the learnings in the program through positive role modelling (e.g., coaching staff model the program skills during training and competitions). The decision to use coaching staff as mentors is supported by the research in Chapter 1 (e.g., Bardel et al, 2010;Holt et al, 2017;Horn et al, 2012;Hurd et al, 2011;McLaren et al, 2015;Smith et al, 2007).…”
Section: Comparison Between the Ris Program And The Friends For Life mentioning
confidence: 99%
See 1 more Smart Citation